Antiviral therapy for influenza in high-risk outpatients: a multicenter observational study of routine clinical practice in Russia - Ivan Tokin; Dmitry Lioznov; Artem Poromov; Tatyana Zubkova; Valerii Tsvetkov; Olesya Nikitina; Olga Pobegalova; Natalia Pshenichnaya; Viktor Renev; Anastasiya Podgornaya (Therapeutic Advances in Infectious Disease)
Background: Influenza is a significant public health challenge, characterized by severe disease progression and considerable societal burden. Patients at high risk of influenza-related complications require special attention in routine clinical practice. Objectives: This study aimed to compare the effects of antiviral treatments for influenza on the incidence of bacterial complications, adverse events, and disease duration in high-risk outpatients. Design: Multicenter, non-interventional, observational cohort study. Methods: The study was conducted during the 2023–2024 influenza epidemic season and included 1867 high-risk outpatients treated with oseltamivir, umifenovir, kagocel, or imidazolyl ethanamide pentanedioic acid. Results: Bacterial complications occurred in 18.87% ( n  = 335) of high-risk patients, with 17.41% ( n  = 309) requiring antibacterial therapy. The hospitalization rate was 1.24% ( n  = 22), and the average disease duration was 8 days. The incidence of bacterial complications varied among treatment groups: oseltamivir (18.96%, n  = 102), umifenovir (12.17%%, n  = 51), kagocel (22.00%%, n  = 110), and imidazolyl ethanamide pentanedioic acid (22.64%%, n  = 72). Adverse events were reported in 4.76% ( n  = 84) of patients, most commonly gastrointestinal disorders (91.67%, n  = 77), followed by allergic reactions (8.33%, n  = 7). The incidence of adverse events was significantly higher in the oseltamivir group compared to other treatments. Conclusion: The etiotropic agents oseltamivir and umifenovir demonstrated comparable efficacy in managing influenza in high-risk patients, as reflected by their impact on bacterial complication rates and disease duration. Both drugs may be recommended for the treatment of high-risk influenza patients.